Records of the Kurds (Cambridge)
13 c. (xlix, 907 s. ; xvi, 769 s. ; xxv, 916 s. ; xxix, 689 s. ; xxvii, 850 s. ; xliv, 801 s. ; xxxiv, 805 s. ; xlii, 860 s. ; xlii, 755 s. ; xxxvii, 652 s. ; xxxii, 611 s. ; xlv, 779 s. ; 36 katlı sayfa harita)